Respuesta :

Answer:

Step-by-step explanation:

Ver imagen josshyaby

Answer:

-4

Step-by-step explanation:

The given equation is

[tex]3x(x+4)=66[/tex]

On simplification we get

[tex]3x^2+12x=66[/tex]

Divide both sides by 3.

[tex]x^2+4x=22[/tex]

[tex]x^2+4x-22=0[/tex]

If a quadratic equation is defined as [tex]ax^2+bx+c=0[/tex], then the sum of solutions is -b/a.

In the above equation a=1, b=4 and c=-22.

Sum of solutions [tex]=-\dfrac{b}{a}=-\dfrac{4}{1}=-4[/tex]

Therefore, the sum of all solutions is -4.